2016
DOI: 10.15447/sfews.2016v14iss2art4
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Economic Costs of Managed Aquifer Recharge in California

Abstract: Groundwater management is important and challenging, and nowhere is this more evident than in California. Managed aquifer recharge (MAR) projects can play an important role in ensuring California manages its groundwater sustainably. Although the benefits and economic costs of surface water storage have been researched extensively, the benefits and economic costs of MAR have been little researched. Historical groundwater data are sparse or proprietary within the state, often impairing groundwater analyses. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 3 publications
1
40
0
Order By: Relevance
“…Large-scale MAR and aquifer storage and recovery (ASR) programs in California, including the Kern and Semitropic Groundwater Banks and the Arvin-Edison water storage district, currently account for only a small fraction (about 0.37 km 3 /year) of California's water supply (DWR et al 2013, Christian-Smith 2013. However, with a median cost of $0.33 per m 3 per year, groundwater recharge is a more cost-effective solution to water availability than seawater desalination ($1.54-$2.43 per m 3 ) or reservoir expansion ($1.38-$2.27 per m 3 ; BOR 2013) (Perrone and Merri Rohde 2016). A recent survey of 202 MAR applications submitted to DWR for funding identified that the most important factor influencing the average annual recharge volume for MAR projects is the availability of water for recharge and storage-highlighting the need for comprehensive assessment of additional water sources for groundwater recharge (Perrone and Merri Rohde 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale MAR and aquifer storage and recovery (ASR) programs in California, including the Kern and Semitropic Groundwater Banks and the Arvin-Edison water storage district, currently account for only a small fraction (about 0.37 km 3 /year) of California's water supply (DWR et al 2013, Christian-Smith 2013. However, with a median cost of $0.33 per m 3 per year, groundwater recharge is a more cost-effective solution to water availability than seawater desalination ($1.54-$2.43 per m 3 ) or reservoir expansion ($1.38-$2.27 per m 3 ; BOR 2013) (Perrone and Merri Rohde 2016). A recent survey of 202 MAR applications submitted to DWR for funding identified that the most important factor influencing the average annual recharge volume for MAR projects is the availability of water for recharge and storage-highlighting the need for comprehensive assessment of additional water sources for groundwater recharge (Perrone and Merri Rohde 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, with a median cost of $0.33 per m 3 per year, groundwater recharge is a more cost-effective solution to water availability than seawater desalination ($1.54-$2.43 per m 3 ) or reservoir expansion ($1.38-$2.27 per m 3 ; BOR 2013) (Perrone and Merri Rohde 2016). A recent survey of 202 MAR applications submitted to DWR for funding identified that the most important factor influencing the average annual recharge volume for MAR projects is the availability of water for recharge and storage-highlighting the need for comprehensive assessment of additional water sources for groundwater recharge (Perrone and Merri Rohde 2016). Among the potential water sources identified by DWR (2017) for groundwater replenishment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Supply‐side opportunities include water transfers (Jenkins et al, ), conjunctive use (Christian‐Smith, ; Scanlon et al, ), and the intentional recharge of aquifers (“managed aquifer recharge”) (Beganskas & Fisher, ). Potential exists to “bank” groundwater using storm water runoff, treated wastewater (Perrone & Rohde, ), or streamflow diverted when river discharges are high (Kocis & Dahlke, ). Augmenting water storage via managed aquifer recharge is often economically favorable relative to further dam construction (Perrone & Rohde, ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential exists to “bank” groundwater using storm water runoff, treated wastewater (Perrone & Rohde, ), or streamflow diverted when river discharges are high (Kocis & Dahlke, ). Augmenting water storage via managed aquifer recharge is often economically favorable relative to further dam construction (Perrone & Rohde, ). Demand‐side options include, foremost, changes to agricultural water demands, as these are projected to be disproportionately important to storage stabilization relative to changes in domestic water demands (Massoud et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Addressing this challenge is proving even more difficult with climate change, existing water policies (e.g., water rights), and aging gray infrastructure (e.g., surface water storage and conveyance infrastructure, such as dams and canals) that limit options. Due to unprecedented and rapid groundwater use worldwide (Famiglietti, ), depleted aquifers provide vast quantities of decentralized “green” storage space underground that can cost‐effectively store alternative water sources (e.g., flood water from rivers, urban stormwater, and treated wastewater) that would otherwise require high energy costs to convey to centralized storage infrastructure, such as dams and reservoirs, located farther upstream (Perrone & Rohde, ). Storing water in underground aquifers by storing water in times of plenty to be later used in drier times can enhance the resiliency and reliability of water supplies.…”
Section: Case Study Example: Pop‐up Wetlands Increase Migratory Bird mentioning
confidence: 99%